Low complexity receivers for single carrier large-scale spatial modulation systems - Cristóvão, Pedro Miguel Carvalho (2019)
The dissertation aims to study the low-complexity receivers for Single Carrier (SC) systems and generalized spatial modulation (GSM) in order to reduce the number of radio frequency (RF) chains used in the emitter and making the system more efficient energetically. In the first instance, the study addressed the use of multiple-Input multipleOutput (MIMO) schemes in conjunction with GSM in SC systemsin order to increase the throughput of a telecommunications network without diminishing energy efficiency. This study was followed by the development of an algorithm based on the alternating Direction method of Multipliers (ADMM) as a low-complexity receiver intending to achieve performances close to the optimal Maximum Likelihood Detector (MLD). The study of the ADMM receptor was done in two stages, the first step consists of the exclusive study of the ADMM receptor is SC systems where the main parameters of the receiver are tested. The second step compared the ADMM receiver with other receivers, namely the MMSE and the Zero Forcing in severe time dispersive environments. The realization of the various simulations with various receivers and scenarios allows to demonstrate that the ADMM can be an efficient and robust alternative. The referred technologies promote the reduction of the ecological footprint and the development of the technologies.